The prevalence of positive urine cultures in 100 dogs with an inactive urine sediment - Rachel Liebelt (Veterinary Evidence, 2019)
Objective: The purpose of this study was to determine the prevalence of positive quantitative urine cultures in dogs with an inactive urine sediment.